Lab experiences for the pharmacy technician - Mohr, Mary E.
Introducing the second edition of Mary Mohr's Lab Experiences for the Pharmacy Technician, a text filled with practical, hands-on laboratory exercises. This book is an ideal laboratory manual for pharmacy technician programs, covering the skills needed to dispense retail prescriptions, inpatient prescription orders, I.V. admixtures, and extemporaneous compounds. In addition, the book covers crucial skills like measuring, mixing, molding, packaging, and labeling medications, all in a reader-focused style that emphasizes engagement and real-world application